2008
DOI: 10.1016/j.juro.2008.02.045
|View full text |Cite
|
Sign up to set email alerts
|

Morphology, Calcium Signaling and Mechanical Activity in Human Ureter

Abstract: To our knowledge this study represents the first measurements of Ca signals in the human ureter obtained during phasic contractions and in response to agonists. Results show that it is controlled by fast propagating Ca waves, which spread rapidly between the muscle bundles, producing regular contractions, and drugs that interfere with excitability or Ca entry through L-type Ca channels have profound effects on Ca signaling and contractility. These data are discussed in relation to the treatment of patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 19 publications
1
12
0
Order By: Relevance
“…This is consistent with our earlier findings concerning the characteristics of Ca signaling and contractility in human ureter (13). Although our sample number is limited in size, the responses to UPEC were consistent and seen in all tissues.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This is consistent with our earlier findings concerning the characteristics of Ca signaling and contractility in human ureter (13). Although our sample number is limited in size, the responses to UPEC were consistent and seen in all tissues.…”
Section: Discussionsupporting
confidence: 93%
“…Ureteric cell membrane excitability is also regulated by calcium-activated K channels (KCa) and Cl channels (8,33,35). The human ureter has been less well-studied but we recently characterized Ca signaling and ion channel expression (13). However, as mentioned above, there are little or no data concerning how these mechanisms are affected by UPEC.…”
mentioning
confidence: 99%
“…For measurements of intracellular calcium, Indo-1 was used as described elsewhere [3, 34]. Loaded ureteric preparations were mounted on 2 stainless steel hooks, one of which was attached to a force transducer, and stretched (passive force being 25%–30% of the active force produced by electrical field stimulation to set optimal length, as spontaneous activity was rarely seen in these preparations).…”
Section: Methodsmentioning
confidence: 99%
“…As the ureters perform an essential function in the transportation of urine from the kidneys to the bladder, efficient ureteric contractility and peristalsis is vital in preventing renal infection. Peristalsis is brought about by propagating action potentials giving rise to global Ca transients, which underlie waves of phasic contractions of the smooth muscle that pass down the ureteric walls [3]. It has been shown that E. coli colonization can impair ureteric peristalsis, which in turn potentiates the infection due to urinary stasis and/or vesicoureteric reflux [4, 5].…”
mentioning
confidence: 99%
See 1 more Smart Citation